Exploring the Association Between Third Molar Agenesis and Carabelli Traits: A Cross-Sectional Study - Isabela Ribeiro Madalena; Heloisa Guimarães Resende; Ariane Beatriz Blancato; Maria Angélica Hueb de Menezes-Oliveira; Flares Baratto-Filho; Poliana Ferreira Santos; Camila Paiva Perin; Thais Vilalba Paniagua Machado do Nascimento; Peter Proff; Christian Kirschneck; César Penazzo Lepri; Erika Calvano Küchler (Dentistry Journal)
Background/Objectives: Dental agenesis is the congenital absence of at least one tooth and has been associated with several other developmental dental conditions, such as morphological dental alterations and Carabelli trait. This study sought to investigate whether third molar agenesis is associated with Carabelli traits in permanent molars. Methods: This was a cross-sectional study that used a convenience sample obtained from the orthodontic records of German patients. Patients with syndromes, oral clefts, congenital alterations including dental agenesis (except agenesis of third molars), and severe cases of bruxism with a loss of tooth tissue were excluded. Teeth with cavitated lesions of dental caries, occlusal wear, restorations, and evident dental deformities were not included in the evaluation. The Carabelli trait was evaluated in the permanent maxillary molars. The Carabelli trait was classified according to its expression for each tooth as either absent, negative, and positive expressions. Third molar agenesis was evaluated only in patients older than 10 years old (based on when initial tooth formation should be visible in the panoramic radiographs). The two-sided Chi-squared test was used to investigate the association between the conditions, using an alpha of 5% (p < 0.05). Results: A total of 155 patients (74 females and 81 males) were investigated; 39 had third molar agenesis and 75 had the Carabelli trait. There was no statistical significance difference between patients with third molar agenesis and those with Carabelli traits in relation to sex (p > 0.05). The Carabelli trait was more common in first molars than in second molars. There was no statistical significant association between third molar agenesis and Carabelli traits (p > 0.05). Conclusions: Third molar agenesis was not associated with the Carabelli trait in the permanent molars in this population.